Desarrollo y Evaluación de una Bebida Kombucha enriquecida con flor de Jamaica (Hibicus sabdariffa) para determinación de análisis fisicoquímico, organoléptico, microbiológico y su viabilidad técnica - Solarte Caicedo, Diana Antonela (2025)
The project investigates as such the production and subsequent evaluation of a kombucha beverage enriched with hibiscus flower (Hibiscus sabdariffa) to analyze its organoleptic, physicochemical and microbiological characteristics. Kombucha is commonly recognized for its probiotic properties, while hibiscus flower provides antioxidants and antimicrobial compounds. In Ecuador, this type of beverage faces obstacles such as lack of knowledge of the product and the absence of regulation, but it offers possibilities for expanding the range of nutritious beverages using indigenous resources. The study is experimental and employs a factorial design that includes two independent variables: the concentration of hibiscus flower (1% and 2%) and the fermentation period (6, 12 and 18 days), analyzing their impacts on key parameters such as pH, acidity, °Brix, microbiological profile and sensory acceptance. The expected results aim to determine the ideal conditions for the production of a healthy and functional beverage, ensuring its quality and safety for consumption